The Effect of Ketamine on Neutrophil-Lymphocyte Ratio (NRL) Levels after Gynecological Laparotomy Surgery - Muhammad Wirawan harahap; Nasrudin Andi Mappaware; Farah Ekawati Mulyadi (Fakultas Kedokteran Universitas Muslim Indonesia, 2026)
Background: Post-surgical pain is a critical issue faced by post-surgical patients. The Neutrophil-Lymphocyte Ratio (NLR) is an index indicating the direction of inflammation. Ketamine is a general anesthetic widely used in surgical procedures that do not require skeletal muscle relaxation. Intravenous ketamine can reduce inflammation through inhibition of the N-methyl-D-aspartate (NMDA) receptor. This demonstrates kematine’s anti-inflammatory properties. Objective: To determine the effect of ketamine on neutrophil-lymphocyte ratio (NLR) levels after gynecological laparotomy. Methods: This experimental study, a clinical trial, used a pre-post-test control design, in which variables were measured before and after the intervention. Data were analyzed using paired t-tests and independent t-tests. Results: The comparison of NLR levels between the control and intervention groups after pynecological laparotomy revealed a significant difference, with a higher increase in the control group compared to the intervention group receiving ketamine (p<0.05). Conclusion: Ketamine can reduce postoperative NLR elevations, thereby reducing inflammation.